2007
DOI: 10.1523/jneurosci.1897-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off between Object Selectivity and Tolerance in Monkey Inferotemporal Cortex

Abstract: Object recognition requires both selectivity among different objects and tolerance to vastly different retinal images of the same object, resulting from natural variation in (e.g.) position, size, illumination, and clutter. Thus, discovering neuronal responses that have object selectivity and tolerance to identity-preserving transformations is fundamental to understanding object recognition. Although selectivity and tolerance are found at the highest level of the primate ventral visual stream [the inferotempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
166
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 79 publications
(164 reference statements)
21
166
0
Order By: Relevance
“…Nevertheless, stimulus size may also influence neuronal responses by providing an overall gain modulation. Consistent with previous reports in IT cortex (Ito et al, 1995;Tanaka, 1996;Zoccolan et al, 2007), we found that many V4 neurons of either type (ie, sensitive to absolute or normalized curvature) showed response gain modulation across transformations of scale and position (Fig. 3, Fig.…”
Section: Response Gain Modulationsupporting
confidence: 92%
“…Nevertheless, stimulus size may also influence neuronal responses by providing an overall gain modulation. Consistent with previous reports in IT cortex (Ito et al, 1995;Tanaka, 1996;Zoccolan et al, 2007), we found that many V4 neurons of either type (ie, sensitive to absolute or normalized curvature) showed response gain modulation across transformations of scale and position (Fig. 3, Fig.…”
Section: Response Gain Modulationsupporting
confidence: 92%
“…It also shows good agreement with other data in V4 on the tuning for two-bar stimuli and for boundary conformations (Pasupathy & Connor, 2001;Reynolds, Chelazzi, & Desimone, 1999). The IT-like units of the model exhibit selectivity and invariance that are very similar to those of IT neurons (Hung, Kreiman, Poggio, & DiCarlo, 2005) for the same set of stimuli, and the model helped explain the tradeo¤ between invariance and selectivity observed in the IT in the presence of clutter (Zoccolan, Kouh, Poggio, & DiCarlo, 2007). Also, the model accurately matches the psychophysical performance of human observers for rapid animal versus nonanimal recognition (Serre, Oliva, & Poggio, 2007), a task that is not likely to be strongly influenced by cortical backprojections.…”
Section: Feedforward Hierarchical Models Of the Ventral Stream Of Thesupporting
confidence: 79%
“…IT was reliably able to decode object identity across a range of transformations, whereas the V4 population performed poorly. Although demonstrations of complex feature selectivity and invariant representations in V4 and IT already exist (Pasupathy and Connor, 2002;Zoccolan et al, 2007), these results provide the first systematic comparison of matched populations across the two different visual areas, documenting an increase in both selectivity and invariance.…”
mentioning
confidence: 73%